Guía didáctica basada en estudios de casos clínicos para el aprendizaje de parasitología en los estudiantes del tercer semestre de laboratorio clínico de la Universidad Nacional de Chimborazo en el año 2022 - Silva Borja, Christian Daniel (2023)
ABSTRACT: The Commission of follow-up to graduates of the Clinical Laboratory career of the National University of Chimborazo in its final report in 2016, suggested on the basis of the survey applied to the graduates of the career, the strengthening of chairs of utmost importance as the chair of Parasitology, having as an aggravating factor that, The standardization of all clinical laboratory careers in the country has led to the decision to reduce the hours of several courses, especially parasitology, in order to allow the creation of other courses, which makes it a real challenge for the teacher to deal with a syllabus of 50 parasites in such a short period of time. The present guide has two fundamental objectives: first, to become a fundamental tool for the educator to improve learning and interest in the course of parasitology; and second, to place the student before real situations of professional life in which he/she has to make the most appropriate decision to collaborate in the diagnosis of parasitic diseases. From the results obtained, it was evidenced that the learning average of parasitology (6.34) after the application of the Methodological Guide based on clinical case studies is higher than the initial average (9.24), it was concluded that the learning of Parasitology in the students of the third semester of the Clinical Laboratory career, of the National University of Chimborazo, improved significantly; therefore, it is recommended that the guide be updated every year identifying the needs of the student and the society.